2020
DOI: 10.1371/journal.pone.0226469
|View full text |Cite
|
Sign up to set email alerts
|

Australian native flower colours: Does nectar reward drive bee pollinator flower preferences?

Abstract: Colour is an important signal that flowering plants use to attract insect pollinators like bees. Previous research in Germany has shown that nectar volume is higher for flower colours that are innately preferred by European bees, suggesting an important link between colour signals, bee preferences and floral rewards. In Australia, flower colour signals have evolved in parallel to the Northern hemisphere to enable easy discrimination and detection by the phylogenetically ancient trichromatic visual system of be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
1
12
2
Order By: Relevance
“…To our knowledge, the relationship between nectar offer and colour as perceived by bees has been explored only in five communities. In three of these (including the present one), some degree of association was found between both parameters (Giurfa et al, 1995;Kantsa et al, 2017), whereas no relationship was detected in the other two (Shrestha et al, 2020). We do not know any other study, apart from the present one, which explores this kind of relationships for pollen offer at community level.…”
Section: Flower Colour: a Trait Weakly Associated With Reward Productioncontrasting
confidence: 48%
See 1 more Smart Citation
“…To our knowledge, the relationship between nectar offer and colour as perceived by bees has been explored only in five communities. In three of these (including the present one), some degree of association was found between both parameters (Giurfa et al, 1995;Kantsa et al, 2017), whereas no relationship was detected in the other two (Shrestha et al, 2020). We do not know any other study, apart from the present one, which explores this kind of relationships for pollen offer at community level.…”
Section: Flower Colour: a Trait Weakly Associated With Reward Productioncontrasting
confidence: 48%
“…The association between rewards and floral cues mediates pollinator services at community level (Herrera, 2020). However, there has been scant research on this relationship at the aforementioned level Kantsa et al, 2017;Shrestha et al, 2020) and the offer both of nectar and of pollen has never been studied. In the Mediterranean Basin, most species flower in the spring, coinciding with maximum richness of insect taxa (Herrera, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…and Bombus sp., as well as phylogenetically separated bee species like the stingless bee Tetragonula carbonaria (Figure 7). Interestingly, such color preferences have been observed to be biologically relevant considering the foraging decisions of naïve bees visiting real flowers (Dyer et al, 2019), providing a plausible explanation for how insect preferences do influence plant fitness and flower color signaling (Giurfa et al, 1995;Shrestha et al, 2020). In addition, floral color loci in the three altitudinal regions of TW we tested consistently and predominantly fall in the sector of bee color space preferred by bees (Figure 7).…”
Section: Discussionmentioning
confidence: 72%
“…In Germany, it was reported that blue flowers more frequently presented higher reward (Giurfa et al, 1995) than alternative flower colors. However, recent work in Australia reports no evidence that any particular color among bee-pollinated flowers was associated with higher nectar rewards (Shrestha et al, 2020), and so currently there is no conclusive evidence of higher rewards being associated with blue flowers. According to Rodríguez-Gironés and Santamaría 2004, interactions among pollinators of different types might interfere with the expression of a color preference.…”
Section: Plant-pollinator Interactionsmentioning
confidence: 93%